Credit cycles with market-based household leverage - Diamond, William; Landvoigt, Tim (Journal of Financial Economics, 2022)
We develop a general equilibrium model in which households’ mortgage leverage is determined by supply and demand forces, where the price of credit impacts the quantity of leverage households choose. Mortgages are supplied by financial intermediaries, who offer households a menu of mortgage contracts whose pricing varies with intermediaries’ equity capital. In the model, growth in the demand for safe assets that replicates the falling interest rates in the 2000s causes an empirically realistic boom in household borrowing, debt-financed consumption, and house prices. This boom results in a larger bust in asset prices and household borrowing in future financial crises.